Efficiency analysis for Peruvian electricity distribution sector: inefficiency’s explicative factors. A study for 2000-2008 - Bonifaz, José Luis (2010)
This paper estimates the inefficiency of Peruvian electricity distribution companies to determine if the expected results from the 90’s reform were met. To do this, we used data for 19 distribution companies for the period 2000 – 2008 using a Cost Stochastic Frontier approach and estimating inefficiency in a one-step procedure. The analysis suggests that private utilities are less inefficient than public Utilities because of better management practices. In other words, private management and investments had been favorable in terms of efficiency for the period studied. Also, regulation changes, especially in 2005, have increased distribution costs and geographical characteristics impact negatively on efficiency, especially in public Utilities. This can be explained by the fact that State investment in difficult areas, with public Utilities operating, imposes additional costs (management and operational) that makes them inefficient. Future investigations should focus in a Region Analysis, for the sake of a bigger Panel sample.